Physicochemical, nutritional and morphological characteristics of native fruits - Augusto-Elías-Peñafiel, Carlos César (2021)
There are many native fruits in Peru containing essential nutrients for health and that have not been fully studied. The objective of this research was to determine the physicochemical, nutritional and morphological characteristics of five varieties of native fruits from the central Andean region and the northern Peruvian jungle: goldenberry (Physalis peruviana), sanky (Corryocactus brevistylus), cocona (Solanum sessiliflorum), yellow pitahaya (Selenicereus megalanthus) and camu camu (Myrciaria dubia). The fruits were washed, peeled, pulped, fleshed, and lyophilized, to determine, using standardized analytical methods, the nutrient content, such as vitamin C, fiber, soluble solids. The goldenberry, sanky and camu camu fruits presented the highest vitamin C content (43.0, 57.1 and 2,780 mg per 100g of fresh weight, respectively), while cocona and pitahaya had 4.54 and 8.0 mg per 100g of fresh weight, respectively. The goldenberry and pitahaya (26.85 and 9.75%) yielded the highest content of reducing sugars. At the same time, goldenberry and cocona reported the highest fiber values (4.9 and 2.5%, respectively). Regarding the content of soluble solids (°Brix), pitahaya and goldenberry showed the highest values (16.2 and 13.3 respectively). In conclusion, the results obtained show that the native fruits studied represent an important source of nutrients that can be beneficial for human health.